Jewish philosophy and political theory to the shoah, some aspects = Żydowska filozofia i teoria polityki wobec Szoa, wybrane aspekty - Greloff, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For many researchers, the new categorical imperative by philosopher Theodor Adorno about thinking and acting in the way so that Auschwitz is never repeated, has become the new starting point for rethinking the rules of practicing the humanities. In the article, I present the postwar history of Jewish thought that has been manifested in the discourse about the Shoah.
Keywords: philosophy; Jews; shoah; history; totalitarism; filozofia; Żydzi; historia; totalitaryzm